Race distribution of Pyrenophora tritici-repentis in relation to ploidy level and susceptibility of durum and winter bread wheat. Issue 4 (4th July 2021) - Wei, Bohan; Despins, Therese; Fernandez, Myriam R.; Strelkov, Stephen E.; Ruan, Yuefeng; Graf, Robert; Aboukhaddour, Reem
Abstract: Tan spot is a destructive disease of wheat caused by the fungus Pyrenophora tritici-repentis ( Ptr ), with most fungal isolates in Canada known to produce the necrotrophic effector (NE) ToxA. In this study, 144 Ptr isolates collected from durum, winter bread wheat, and grasses in western Canada were evaluated for race classification on a host differential set. The susceptibility of 114 durum and winter bread wheat genotypes to Ptr races 2 (R2), 3 (R3), and 5 (R5), producing the NEs ToxA, ToxB, and ToxC, respectively, was evaluated in bioassays. The host genotypes were tested for the presence of Tsn1, the ToxA-sensitivity gene, by PCR analysis. Race composition varied based on the host type and ploidy level from which the isolates were recovered. R1 (ToxA and ToxC-producer) and R2 were predominant on wheat and occurred in equal frequency on durum, while R1 occurred twice as frequently as R2 on winter bread wheat. R3 was recovered only from durum wheat, and the non-pathogenic R4 was the only race recovered from grasses. Susceptibility to R2 and R3 was more common in Canadian than in European wheat, while susceptibility to R5 was more common in durum and European wheat. Tsn1 amplified at a higher percentage in Canadian (51.2% in winter bread, 59.0% in durum) vs. European (20.5%) wheat genotypes. The presence of Tsn1, however, did not result in susceptibility to ToxA-producing isolates in 35.9% of durum genotypes, indicating that other factors are involved in the Ptr -durum interaction and that ToxA- Tsn1 may not play a significant role in tetraploid wheat.